PENERAPAN STATISTICAL QUALITY CONTROL (SQC) PADA PENGOLAHAN KOPI ROBUSTA CARA SEMI BASAH - Andrew Setiawan Rusdianto; Noer Novijanto; Rosy Alihsany (Faculty of Agricultural Technology, University of Jember, 2011)
PT. J.A. Wattie is local plantation which process robusta coffee in Jember. The main problem of Indonesian coffee is quality, which can not fulfill the requirement of international market quality. The several factors that influence coffee quality are harvest, sanitation, productionprocesses, place and equipment. Statistical quality control is method to control production process stability, where PT. J.A. Wattie did not apply in coffee productionprocess. The objectives of this research are identify quality output at each stage of processes; observe the correlation of production process and coffee quality based on statistical quality control.Grading and hulling processes according to control chart showed that the process was under control because data plot to be present in interval upper and lower control limit. Pulping and washing processes were out of control because some data plot to be present in outside of upper control limit or lower control limit.Washing process showed other pattern because more than four (4) data make increasing or decreasing pattern. Increasing or decreasing patterns can be indicator of abnormality processes. Abnormality of washing and pulping processes were resulted from the pulper and washer. The rare maintance of pulper and washer can be factor that makes abnormality process.Keywords: coffee, robusta, quality, statistical quality control